Answer:
Total cost of Theo's purchases in terms of k and p=2.49(k + p) + 5.99
Step-by-step explanation:
Cost of k key chain=$2.49
Cost of p photo frames=$2.49
Cost of a T-shirt=$5.99
Total cost of all items=cost of k key chain + cost of p photo frame + cost of The shirt
=2.49k + 2.49p + 5.99
Factorise
2.49 is common to both k and p
=2.49(k + p) + 5.99
Total cost of Theo's purchases in terms of k and p=2.49(k + p) + 5.99
The probability that the sum of the dice is 7 is 1/2 because there are only three combinations that result in the sum of 7: (1,6)(2,5) and (3,4). But there are 6 possible outcomes( this is if you don’t add reverse combinations such as 1,6 and 6,1) so the probability would be 3/6 or 1/2
Answer:
The real solutions are
![x=\sqrt[6]{6}\approx 1.35\\\\\:x=-\sqrt[6]{6}\approx -1.35](https://tex.z-dn.net/?f=x%3D%5Csqrt%5B6%5D%7B6%7D%5Capprox%201.35%5C%5C%5C%5C%5C%3Ax%3D-%5Csqrt%5B6%5D%7B6%7D%5Capprox%20-1.35)
Step-by-step explanation:
The solution, or root, of an equation is any value or set of values that can be substituted into the equation to make it a true statement.
To find the real solutions of the equation
:
![\mathrm{Divide\:both\:sides\:by\:}5\\\\\frac{5x^6}{5}=\frac{30}{5}\\\\\mathrm{Simplify}\\\\x^6=6\\\\\mathrm{For\:}x^n=f\left(a\right)\mathrm{,\:n\:is\:even,\:the\:solutions\:are\:}x=\sqrt[n]{f\left(a\right)},\:-\sqrt[n]{f\left(a\right)}\\\\x=\sqrt[6]{6}\approx 1.35\\\\\:x=-\sqrt[6]{6}\approx -1.35](https://tex.z-dn.net/?f=%5Cmathrm%7BDivide%5C%3Aboth%5C%3Asides%5C%3Aby%5C%3A%7D5%5C%5C%5C%5C%5Cfrac%7B5x%5E6%7D%7B5%7D%3D%5Cfrac%7B30%7D%7B5%7D%5C%5C%5C%5C%5Cmathrm%7BSimplify%7D%5C%5C%5C%5Cx%5E6%3D6%5C%5C%5C%5C%5Cmathrm%7BFor%5C%3A%7Dx%5En%3Df%5Cleft%28a%5Cright%29%5Cmathrm%7B%2C%5C%3An%5C%3Ais%5C%3Aeven%2C%5C%3Athe%5C%3Asolutions%5C%3Aare%5C%3A%7Dx%3D%5Csqrt%5Bn%5D%7Bf%5Cleft%28a%5Cright%29%7D%2C%5C%3A-%5Csqrt%5Bn%5D%7Bf%5Cleft%28a%5Cright%29%7D%5C%5C%5C%5Cx%3D%5Csqrt%5B6%5D%7B6%7D%5Capprox%201.35%5C%5C%5C%5C%5C%3Ax%3D-%5Csqrt%5B6%5D%7B6%7D%5Capprox%20-1.35)
if there were 100 questions then 76 were correct, and 24 incorrect, you can simplify and rearrange the fraction depending on how many questions there were,
Answer:
Step-by-step explanation:
Simplify the expression -4x^2(3x − 7).
A. -12x^3 + 28
<h2>B. -12x^3 + 28x^2<= your answer</h2>
C. -12x^3 − 28
D. -12x^3 − 28x^2